Phương pháp chế tạo, cấu trúc và tính chất quang của vật liệu huỳnh quang xCaO.MgO.2SiO2:Eu2+ - Hảo Tâm, Tống Thị; Hùng, Nguyễn Duy; Chiến, Nguyễn Đức; Huy, Phạm Thành (Vietnam Journal of Chemistry, 2014)
Phosphor materials based on rare-earths ion doped akermanites have recently attracted interest of many scientist groups in and outside the country due to their potential applications in white light emitting diodes. In this paper we present results of our research on the fabrication, structure and optical properties of  xCaO.MgO.2SiO2: Eu2+ phosphor - a phosphor that has the ability to emit light both in the blue and green regions. The method used for preparation of the ​​material is co-precipitation method. The obtained phosphor material has xCaO.MgO.2SiO2 akermanites network structure with high chemical and thermal stability. Under an UV excitation, the phosphors showed two strong broad emission bands, namely blue and yellowest-green bands, peaking at 450 nm and 530 nm, respectively, which can be attributed to the transitions of the Eu2+ ion in the host lattice. The material is therefore very promising for applications in lighting device in general and especially for white light emitting diodes to its two emission bands which are two of three primary colors of the white light. Keywords: xCaO.MgO.2SiO2:Eu2+ phosphor, PL, LED